Effect of cell shape on dielectric behavior of fission yeast - Asami, K. (Biochimica et Biophysica Acta (BBA) - General Subjects, 1999)
In order to study the effect of cell shape on dielectric behavior of cell suspensions, a temperature sensitive cell division cycle mutant, cdc25-22, of Schizosaccharomyces pombe was used, whose cell length was varied by cultivating at the restrictive temperature. The dielectric dispersion of the cells in suspension was mainly composed of two subdispersions. The low-frequency subdispersion depended on the cell length, whereas the high-frequency subdispersion was independent of it. The cell shape effect was qualitatively simulated by an ellipsoidal cell model.